Pengembangan Media Pembelajaran Arsip Digital Berbasis Microsoft Access pada SMK Program Keahlian Manajemen Perkantoran Dan Layanan Bisnis (MPLB) - Mery Octavia Sari; Roni Faslah; Nadya Fadillah Fidhyallah (Jurnal Pendidikan Dirgantara, 2026)
This research aims to develop and assess the feasibility of Microsoft Access-based learning media as a digital archive tool. Using a Research and Development (R&D) approach, the study follows the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The participants included one media expert, one material expert, one language expert, and 33 class X MPLB students at SMK Negeri 49 Jakarta. Data collection was conducted through observations, interviews, and questionnaires rated on a Likert scale, evaluated by experts and students. The findings show that: 1) The Microsoft Access-based media, developed for the MPLB basics subject, can be run on laptops or computers; 2) The media suitability received an 81.3% rating ("Very Appropriate"), material suitability 89.3% ("Very Appropriate"), and language suitability 100% ("Very Appropriate"). In the trials, individual testing with three students yielded 89.6% ("Very Eligible"), small group testing with 10 students received 75.7% ("Decent"), and field testing with 20 students reached 86.8% ("Very Eligible"). 3) The product is deemed highly suitable by experts, with strong support from small group and field trials, confirming its effectiveness as a learning tool.